FENOMENA LARANGAN BEKERJA DI LUAR RUMAH BAGI ISTRI DI DESA SANTAN TENGAH KECAMATAN MARANGKAYU KABUPATEN KUTAI KARTANEGARA DITINJAU DARI HUKUM ISLAM DAN HAM - Masna Eka Wahyuni; Alfitri; Aulia Rachman (Fasya UIN Sultan Aji Muhammad Idris Samarinda, 2026)
This study was motivated by the phenomenon of husbands prohibiting their wives from working outside the home, which still occurs in Santan Tengah Village. The research aims to analyze the reasons behind husbands' restrictions on their wives' employment and to examine the practice from the perspectives of Islamic Law and Human Rights. This study employed an empirical normative legal approach using qualitative methods. Data were collected through interviews and documentation involving four married couples and analyzed using the perspectives of Islamic jurisprudence, particularly Fatawa al-Mar'ah al-Muslimah, Law Number 39 of 1999 on Human Rights, the Universal Declaration of Human Rights (UDHR), and the 1945 Constitution of the Republic of Indonesia. The findings reveal that husbands prohibit their wives from working due to concerns regarding childcare responsibilities, personal safety, workplace distance, and the preservation of family harmony. From the perspective of Islamic Law, such restrictions are considered permissible when intended to safeguard family welfare (maslahah) and comply with Islamic legal principles. However, from the Human Rights perspective, these restrictions may limit women's rights to employment, self-development, gender equality, and an improved standard of living. Therefore, the study demonstrates a difference between Islamic Law, which prioritizes family welfare, and Human Rights, which emphasize women's individual rights to work.